Electronic structure modulation of MnO2 by Ru and F incorporation for efficient proton exchange membrane water electrolysis. Issue 41 (3rd October 2022) - Kim, Dongwon; Voronova, Anastasiia; Kim, Sol; Kim, Jin Young; Park, Hee-Young; Jang, Jong Hyun; Seo, Bora
Abstract : Incorporation of Ru and F into α-MnO2 tuned the electronic structure of α-MnO2 and led to the development of a highly active, cost-effective anode catalyst for proton exchange membrane water electrolysis. Abstract : Hydrogen is a sustainable energy carrier that can be produced via water electrolysis (WE). However, the use of precious metals as anode catalysts increases the cell stack price and hinders the practical implementation. Therefore, MnO2 has been introduced as a catalytic support material to maximize the utilization of precious metals at a given loading. However, their oxygen evolution reaction (OER) activities remain unsatisfactory owing to lack of precise structural control. Here, Ru and F incorporation successfully modulates the electronic structure of MnO2 for application to proton exchange membrane water electrolysis (PEMWE). Optimization of the synthesis conditions produced a (Mn0.94 Ru0.06 )O2 :2.5F catalyst, which showed a high mass activity. X-ray spectroscopic and electrochemical characterizations revealed that the OER activity increased with the Mn 3+ /Mn 4+ ratio and oxygen vacancies. In addition, practical applicability was demonstrated by applying (Mn0.94 Ru0.06 )O2 :2.5F as the anode catalyst in a PEMWE cell.